Die Reformperspektive der EU-Finanzverfassung nach den Beschlüssen zur Agenda 2000 - Friedrich Heinemann (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1999)
A rational financial constitution of the EU should be able to fulfil redistributive objectives at minimum costs. The present financial system of the Community is not compatible with this requirement. After the decisions of the European Council in Berlin on the Agenda 2000 the fundamental flaw of the system remains: the dominance of distributive objectives over allocative decisions. On the basis of this diagnosis options for future reforms are analyzed. The hope that larger budgetary competences for the European Parliament will lead to more financial rationality proves to be weakly founded. The reform package suggested by the Scientific Council at the German Federal Ministry of Economics includes with cofinancing and contributions depending on voting power sensible elements. Its shortcomings originate mainly from an implicit negation of any necessity to redistribute between member countries. In contrast to that the setup of a compensation fund is recommended that would be advisable for a cost-effective realization of politically defined redistributive objectives. The paper concludes with an outlook on the consequences of a continuing incapacity to reform the financial constitution: Eastern enlargement will be in danger and the pressure will increase to open new financial sources for the EU in form of a competence to issue debt and to impose taxes.
Keywords: H77; H61; F36; 330; Agenda 2000; European Union; eastern enlargement; Community budget; Finanzreform; Finanzföderalismus; EU-Strukturfonds; Public Choice; Europäische Integration; EU-Staaten